The diaspora and socio-economic roles of Muslim migrants in the City of Dasmariñas, Philippines - R. Rocina, Jose Aims (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study focuses on the factors of migration of Muslims from Mindanao to Luzon, specifically the City of Dasmarinas, Philippines. It also provides data on the present roles of such migrants to the development of the city and their thematic traits as a people. Culled mainly from 12 interviews and with analysis adapted from Moustakas, et.al. Model; the main reason for their migration according to interviews is the search for new opportunities; their belief that they would earn more in the establishments of the city. Their decision to migrate is also influenced by persons close to them such as relatives. The interviewees have quickly adapted to their new environment by traveling together and settling with their families. Ethnographic approach unraveled that aside from paying taxes to the coffers of the city and rent to its businesses, Muslim migrants have contributed to the city’s progress by engaging in work; providing aid during calamities, charitable works and cheaper products to the city’s inhabitants. Employing a qualitative case method, and using informal and in-depth tools; the study concludes that the Muslims of Dasmarinas have not only enriched the socio-economic aspects of the city, but have also greatly contributed to its over-all growth and productivity.